Don't forget the science. (16th March 2013) - Maskell, Duncan; Argyle, David; Cameron, Ewan; England, Gary; Price, Jo; Herrtage, Mike; Reid, Stuart; Dawson, Susan
Abstract : Veterinary practice must be based on scientific principles if the profession is to remain credible and relevant, say Duncan Maskell, David Argyle, Ewan Cameron, Gary England, Jo Price, Mike Herrtage, Stuart Reid and Susan Dawson